Endometrioma: A Concern for fertility - Baral , J; Acharya , P; Rana , A; Gurung , G (Journal of Institute of Medicine Nepal, 2014)
Introduction: Endometriosis is a complex disease of young women in reproductive age, responsible for endometriosis-associated pelvic pain (EAPP) because of the deeply infiltrating endometriosis (DIE). There has been significant successful revolution in the diagnosis and the management both surgical and medical where medical treatment both pre and post-operatively has been documented as gain for pain relieve and fertility promotion. Methods: Retrospective study was done for a period of 4 years, April 2009 - 2013, in Department of Gynecology and Obstetrics, TU Teaching Hospital, using Operation Register obtaining files from Medical Record Section. All the cases exposed to operative management endometrioma were noted for size, adhesions and association with other gynecological condition and the type of surgical approach used for future fertility preservation. Results: There were 77 cases of chocolate cysts, representing 3.2% of major gynecological surgery, in age up to 30 years being 21 (27%) as compared to those above the age of 30. Adhesion were omnipresent in all cases [mild 20 (26%) and dense adhesions and 57 (74%). Irrespective of the size of chocolate cysts; 3-5 cm (27); >5-10 cm (40); 10-15 cm (9), 15-20cm (1); associated was myoma in 14 (18%). Confined to 36% infertility were total 28 [Primary infertility (14); Secondary infertility (14)]. Adhesion was dense in all cases of primary infertility and in 12/14 cases of secondary infertility, yet forward anticipation in primary (9) and cases of secondary (6) infertility cases [after deducting, 13: hysterectomy (11) and bilateral ovarian removal (2)] along with 8/9 cases in unmarried [expecting, hysterectomy (1)] but may not be rewarding in cent percent. Conclusion: Endometrioma noted to create adhesion in one and all cases, expected to enhance on operative exposure, need coverage by favorable medication before and after semiconservative surgical approach to overcome associated adverse fertility prognosis.